STRATEGI PEMILIHAN SUBCONTRACTOR UNTUK MENINGKATKAN KINERJA BISNIS PADA INDUSTRI KONSTRUKSI - Yunan Wijaya; Susilo Toto Raharjo (Jurnal Akuntansi dan Pajak, 2023)
In the world of work it is demanded to complete work quickly, effectively, efficiently and with the best possible quality, including in the construction industry. Sometimes the project requires a workforce that is more or more skilled than what is currently owned to improve the company's performance. So that a strategy emerged to delegate work to other companies.However, if there is cooperation between the two parties, there will be the potential for conflict between the main contractor and the subcontractor. Therefore a strategy is needed to overcome conflicts that occur between the main contractor and subcontractors, then a strategy is also needed to avoid these conflicts. In choosing a subcontractor, a strategy is also needed so that from before starting work until its completion it can run smoothly. Keywords: Main Contractor and Subcontractor, Construction Industries, Conflict Between Main Contractor and Subcontractor, Choosing Subcontractor, Company Performance